Timing and Tectonic Setting of the Gaoaobei Tungsten-Molybdenum Deposit in Nanling Range, South China - Li, Jianfeng; Ma, Kemeng; Lu, Youyue; Fu, Jianming; Cheng, Shunbo; Li, Yuan; Li, Chuanbiao (Journal of earth science (Wuhan, China), 2024)
The Gaoaobei tungsten-molybdenum deposit is a newly discovered large-scale quartz-vein-type deposit in the Nanling metallogenic belt in South China. The ore bodies are hosted in the Indosinian granites and the Cambrian Xiangnan Group slates and are controlled by NWW-oriented faults, which are obviously different from the “five-story building” model in southern Jiangxi Province. The magmatic rocks in the study area are dominated by medium- to coarse-grained biotite monzogranite, with a few NW-oriented fine-grained granite dykes. The medium- to coarse-grained biotite monzogranite and fine-grained granite dykes have zircon U-Pb ages of 229.4 ± 1. 9 Ma (MSWD = 1.5) and 164.9 ± 3.3 Ma (MSWD = 0.75), respectively, corresponding to the Indosinian and Yanshanian magmatism. The monzogranites have higher contents of FeO, CaO, K 2 O, P 2 O 5 , and TiO 2 , while the granite dykes have slightly higher contents of SiO 2 , Al 2 O 3 , MnO, and Na 2 O. Their A/CNK values are 1.11–1.75 and 1.19–2.25, and the contents of CIPW normative corundum are 1.71%–6.66% and 2.41%–9.50%, suggesting both the monzogranites and granite dykes are S-type granite. The total amount of rare earth elements in the monzogranites (from 84.7 ppm to 129 ppm) is slightly lower than that in the granite dykes (from 128 ppm to 133 ppm). The Eu/Eu* values range from 0.12 to 0.30 in monzogranites and from 0.001 1 to 0.001 3 in granite dykes, indicating the fine-grained granites underwent more intense fractional crystallization. The monzogranite and granite dykes have high 87 Sr/ 86 Sr i values of 0.716 9–0.719 3 and 0.728 25–0.728 80, low ε Nd ( t ) values ranging from −10.2 to −9.6 and from −11.5 to −11.4, and T DM2 ages of 1 835–1 785 and 1 957–1 946 Ma, respectively. These isotope data indicate their origin from the remelting of the Paleoproterozoic crustal materials. Combined with regional geology, it is concluded that the medium- to coarse-grained biotite monzogranite was formed in a post-collisional extensional environment. In addition, 40 Ar- 39 Ar dating of the greisen type tungsten-molybdenum ore gave consistent plateau age of 164.0 ± 1.2 Ma, isochronal age of 162.0 ± 2.4 Ma and anti-isochronal age of 161.4 ± 1.8 Ma. Combined with the published molybdenite Re-Os age, the Gaoaobei tungsten-molybdenum deposit was formed at ∼164 Ma, which is inferred to be genetically related to the contemporaneous finegrained granite dykes (165 Ma). The deposit was likely formed during the large-scale magmatism and mineralization event in the early Yanshanian of the Nanling Range in an intra-continental extensional environment caused by the subduction of the paleo-Pacific plate. The late and small granite dykes within the large granite plutons thus require further attention during mineral prospecting in the regions.